Nanoemulgel activity of Binahong (Anredera cordifolia (Ten.) Steenis) leaf extract againts wound healing of hyperglycemic rats - Magfirah Septiani Yusuf; Iis Wahyuningsih; Sapto Yuliani (Universitas Ahmad Dahlan, 2023)
Hyperglycemia is associated with long-term damage, leading to the onset of wounds. The content of flavonoid compounds, steroids and saponins in Binahong leaves (Anredera cordifolia (Ten). Steenis) plays a role in the healing of diabetic wounds. The effectiveness of the active substance of the natural material is influenced by the large size of the particles, due to the presence of barier skin membranes. Nanoemulgel is an emulsion preparation with a droplet size of 1-100 nm which is suspended in a hydrogel. This study aims to determine the wound healing activity of diabetes in nanoemulgel preparations of binahong leaf extract (Anredera cordifolia (Ten.) Steenis) with its extract in male rats wistar hyperglycemia. The study was divided into 4 groups each consisting of 6 mice with diabetic wounds who got each a negative control group (glucose + nanoemulgel base), a positive control group (glucose + Madecassol 1%), a test group 1 (glucose + nanoemulgel, and a test group 2 (glucose + EDB). Treatment is carried out 2 times a day for 16 days. KGD measurements are carried out on the 0th, 1st, 5th, 14th and 21st days, and measurements of the diameter of the wounds are carried out on the 1st, 5th, 14th and 21st days. The KGD measurement results of the EDB nanoemulgel group decreased KGD by 52.91% on day 16 compared to the extract group which decreased by only 30.51% until the 16th day. The closure of the diabetic wounds of the EDB nanoemulgel group experienced closures of up to 52.91% compared to extracts that experienced closure of only 30.51% on day 16. The results of the one-way anova statistics showed a significant difference in the value of the decrease in kgd of the nanoemulgel preparation and its extract with the sig value. 0.045 and significant differences to the wound closure diameter of the diabetic EDB nanoemulgel group and its extract.